Risk Assessment of Hemorrhage of Posterior Inferior Cerebellar Artery Aneurysms in Posterior Fossa Arteriovenous Malformations. Issue 4 (18th May 2017) - Hung, Alice L; Yang, Wuyang; Braileanu, Maria; Garzon-Muvdi, Tomas; Caplan, Justin M; Colby, Geoffrey P; Coon, Alexander L; Tamargo, Rafael J; Huang, Judy
Abstract: BACKGROUND: Posterior fossa arteriovenous malformations (AVMs) are associated with increased risk of rupture and severe consequences from such rupture. The hemorrhagic risk of prenidal aneurysms (anr) on the posterior inferior cerebellar artery (PICA) may exceed that of the AVM in posterior fossa AVMs fed by PICA (PICA-AVM). OBJECTIVE: To characterize the relative risks of aneurysm and AVM hemorrhage in patients with posterior fossa AVMs. METHODS: We retrospectively reviewed patients diagnosed with AVM. Patients with posterior fossa AVMs were divided into 3 groups: PICA-AVM with prenidal aneurysm (PICA-AVM-anr group), PICA-AVM without prenidal aneurysm (PICA-AVM group), and AVMs without PICA feeder with/without aneurysm (AVM-only group). Patient and lesion characteristics and treatment outcomes were compared. ANOVA and chi squared tests were used for statistical analyses. RESULTS: Our cohort included 85 patients. Mean age was 45.3 ± 18.1 yr, with 43(50.6%) female patients. Fifty-one patients (60.0%) had hemorrhagic presentation, and 27 (31.8%) experienced acute hydrocephalus. Patients in the PICA-AVM-anr group (n = 11) were more likely to present with aneurysmal subarachnoid hemorrhage (SAH; P = .005) and less likely to have AVM rupture ( P < .001). Ten (90.9%) patients presented with hemorrhage, 6 (60.0%) of which resulted from aneurysm rupture. Of these 6, 5 (83.3%) had acute hydrocephalus. No patients with AVM rupture had hydrocephalus. Eight (72.7%) received aneurysm treatment prior to AVM treatment. There were no significant differences in post-treatment outcomes dependent on treatment order. CONCLUSION: In addition to relatively higher risk of AVM rupture from infratentorial location and prenidal aneurysm, a higher risk of aneurysm rupture rather than AVM rupture was observed in patients with PICA-AVM-anr complex.